TANGGUNG JAWAB PEJABAT PEMBUAT AKTA TANAH TERHADAP AKTA JUAL BELI TANAH YANG TELAH DIBEBANI HAK TANGGUNGAN (STUDI PUTUSAN PENGADILAN NEGERI TEGAL NOMOR 29/PDT.G/2017/PN.TGL) - Adi Tri Atmaja; Gunawan Djajaputra (Jurnal Hukum Adigama, 2020)
Land Deed Official (PPAT) deeds are authentic deeds that have absolute power regarding matters or events mentioned in the deed. Therefore, the deed made by PPAT must be made in such a way that it can be used as a strong basis for registration of transfer of rights. The settlement of problems that arise as a legal consequence of the purchase of land that is being encumbered with a Mortgage is based on the provisions of Article 6 of the Mortgage Law. The problem faced in writing this thesis is how the responsibility of PPAT for the deed of sale and purchase of land that has been burdened with mortgage rights (Tegal District Court Decision Study Number 29/Pdt.G/2017/PN.Tgl). The research method used in writing this thesis is normative legal research. The results show that PPAT can be held accountable for administrative, civil, and criminal responsibility for the issuance of a deed of sale and purchase of land rights bound by collateral without an original certificate. PPAT is obliged to refuse to make a sale and purchase certificate if the parties do not provide the original certificate. If a PPAT continues to issue the sale and purchase deed, the PPAT concerned has neglected his obligations in carrying out his position either due to an element of intent, negligence, and / or negligence.